Trends in Acarology Proceedings of the 12th International Congress - Sabelis, Maurice W.; Bruin, Jan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Acari are everywhere and acarologists go after them $1 (Bsome aiming to explore the bewildering diversity of the mites and ticks, others trying to understand the how and why of their being. For the past 50 years, the International Congress of Acarology has been the foremost forum for worldwide communication on the knowledge of mites and ticks, helping researchers and students to look beyond the borders of their disciplines. Many mites and ticks have economic consequences as they are pests of agricultural, veterinary and medical importance, and several species have become model organisms for studies in modern biology. The 96 contributions to Trends in Acarology $1 (Breflecting a vast variety of disciplines, such as molecular biology, biochemistry, physiology, microbiology, pathology, ecology, evolutionary biology, systematic biology, soil biology, plant protection, pest control and epidemiology $1 (Bhave all been reviewed and carefully edited. The resulting voIume contains a wealth of new information, that may stimulate research for many years to come.s
PLENARY OPENING LECTURE -- PHYLOGENY AND TAXONOMY OF ACARI -- MORPHOLOGY OF ACARI -- BIOGEOGRAPHY AND BIODIVERSITY OF ACARI -- PHYSIOLOGICAL ACAROLOGY -- CHEMICAL ACAROLOGY -- EVOLUTIONARY AND ECOLOGICAL ACAROLOGY: INTRASPECIFIC VARIATION -- EVOLUTIONARY AND ECOLOGICAL ACAROLOGY: REPRODUCTIVE BEHAVIOUR AND SOCIALITY -- EVOLUTIONARY AND ECOLOGICAL ACAROLOGY: DEMOGRAPHY, DIAPAUSE AND DISPERSAL -- ECOLOGICAL ACAROLOGY: ASSOCIATIONS WITH INSECTS -- ECOLOGICAL ACAROLOGY: INVASIVE SPECIES -- AGRICULTURAL ACAROLOGY: BIOLOGICAL CONTROL -- AGRICULTURAL ACAROLOGY: PESTICIDES AND BIOLOGICAL CONTROL -- AGRICULTURAL ACAROLOGY: HOST PLANT EFFECTS AND DAMAGE -- VETERINARY ACAROLOGY -- ACARICIDES -- ACAROLOGICAL TOOLS.
Keywords: Life sciences; Agriculture; Animal ecology; Biodiversity; Invertebrates; Entomology; Life Sciences; Invertebrates; Entomology; Animal Ecology; Biodiversity; Agriculture